Epidemiological characterization of notified Hepatitis B cases in the state of Piauí between 2008 and 2018 (Research, Society and Development, 2020)
Infection with hepatitis B virus (HBV) remains a global public health problem because of its high transmissibility. To analyze the epidemiological data of hepatitis B in the state of Piauí, based on the cases notified from 2008 to 2018, seeking to contribute to the adoption of new health proposals, related to the prevention and control of the disease. This is a retrospective, descriptive study with a quantitative approach, carried out with data collected on the website of the Department of Informatics of the Unified Health System (DATASUS), based on the cases registered in the Information System for Notifiable Diseases (SINAN). Regarding gender, it was observed that males had a greater number of cases, corresponding to 53% of the total. Regarding the age group, the highest percentage of those infected with hepatitis B was between 20 and 39 years old, representing 47.54% of the cases. According to the area of residence of the individuals, it was found that the urban area obtained the highest index when compared to the others, corresponding to 77.05%. Regarding the form of contagion of individuals, the highest percentage recorded was Ign/Branco with 56.8%. With regard to education, we can see that 20.1% of the cases correspond to individuals with complete high school. Thus, it is necessary to strengthen health promotion and prevention activities, with the aim of guiding the entire population, especially the most disadvantaged, on care against this virus.